Analysis of Traffic Congestion Cause U-turn Location (Case study: U-Turn in Panbil Industrial Estate U-Turn, Batam) - Havila Elysia; Usmanul Hayadi Umar (Fakultas Teknik Sipil dan Perencanaan, 2023)
One of the nicknames of the Batam City is an industrial city, a city that experiences very fast population growth every year, this also affects the volume of vehicles on the main roads of the Batam City, one of which is the traffic on Jalan Ahmad Yani to be precise in front of the Panbil Industrial estate gate. Access to the Panbil Industrial Estate is located right in front of the u-turn location, drivers heading to Panbil Industrial Estate from the south and drivers wanting to leave Panbil Industrial Estate heading south, two directions with the same route which will cause congestion and queues for vehicles moving in the same direction as the vehicle before maneuvering to turn around or for vehicles on other lanes as a result of the vehicle's maneuvers. This study aims to determine how much influence the vehicle's turning maneuver has on road performance, as well as evaluate the traffic characteristics due to U-Turn.